PENGEMBANGAN MICROLEARNING VIDEO 360° PADA FENOMENA KONTRAKSI PANJANG - Anggraeni, Risma; Budi, Esmar; Fitri, Upik Rahma (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
Currently educators are faced with great challenges, where educators are required to develop human resources by utilizing technology, especially in modern physics learning in the era of Society 5.0. This research aims to design and develop a 360° video microlearning that is feasible to use as a learning media for modern physics courses on the topic of length contraction to support effective learning in class. This research is a type of development research using the ASSURE model. In this study, the sample used consisted of 60 respondents taken from 1 class of physics education students and 1 class of UNJ physics students. This study shows that the use of 360° videos significantly improves students' understanding of complex physics concepts and increases their involvement in the learning process. The impact can be seen from the improvement of learning quality that creates an interactive and engaging learning experience. The final product of this research is a 360° video presented using the YouTube platform and can be accessed easily by students using supporting electronic devices. The 360° video has gone through the feasibility test stage to media experts and material experts. The results of the product feasibility test by media experts with a percentage of 93.75% get the results of "Very Feasible", as well as by material experts with a percentage of 87.5% get the results of "Very Feasible".